Peran Yayasan Baitul Maal sebagai Program Corporate Social Responsibility PT PLN (Persero) ULP Bangkir dalam Meningkatkan Kesejahteraan Masyarakat dari Perspektif Ekonomi Islam - Sulistyawan, Dony; Anwar , Khoirul; Rahmadani, Arief (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Corporate Social Responsibility (CSR) is the social responsibility that must be implemented by companies in Indonesia in accordance with government regulations, aimed at empowering communities and improving the quality of life and the environment, which in turn can enhance the company's image. This study examines the implementation of CSR at PT PLN (Persero) ULP Bangkir through the Yayasan Baitul Maal PLN (YBM PLN) program from an Islamic economic perspective. The method used is a descriptive qualitative approach, with data collection through interviews, documentation, observation, and literature study. Data analysis is conducted using the Miles and Huberman model, which includes data collection, data reduction, data presentation, and conclusion drawing. The results show that the CSR program of PT PLN ULP Bangkir has implemented Islamic economic principles, such as al-adl (justice), al-ihsan (kindness), amanah (trust), and benefit. These programs have had a positive impact in the fields of education, health, and economy, as well as strengthening relationships with stakeholders. This study recommends that PT PLN ULP Bangkir continue to enhance its Islamic-based CSR programs, particularly in environmental preservation, to achieve broader impacts and create a sustainable and responsible business model.